2020
DOI: 10.1186/s12872-020-01434-z
|View full text |Cite
|
Sign up to set email alerts
|

The COngenital HeARt Disease in adult and Pulmonary Hypertension (COHARD-PH) registry: a descriptive study from single-center hospital registry of adult congenital heart disease and pulmonary hypertension in Indonesia

Abstract: Backgrounds: The COngenital HeARt Disease in adult and Pulmonary Hypertension (COHARD-PH) registry is the first registry for congenital heart disease (CHD) and CHD-related pulmonary hypertension (PH) in adults in Indonesia. The study aims to describe the demographics, clinical presentation, and hemodynamics data of adult CHD and CHD-related PH in Indonesia. Methods: The COHARD-PH registry is a hospital-based, single-center, and prospective registry which includes adult patients with CHD and CHD-related PH. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…In the COHARD-PH registry, most patients with ASD did not diagnosed properly in childhood and consequently develop complication of PH, Eisenmenger syndrome and right heart failure. 8 This study was the first to assess the association between serum sST2 level, taken from pulmonary artery, with S' parameter in ASD-associated PH. Previous research had shown a significant correlation between serum sST2 with RV systolic function parameters,i.e Tricuspid Annular Plane Systolic Excursion (TAPSE) and Right Ventricle Fractional Area Change (RVFAC), in the PH subjects population due to chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the COHARD-PH registry, most patients with ASD did not diagnosed properly in childhood and consequently develop complication of PH, Eisenmenger syndrome and right heart failure. 8 This study was the first to assess the association between serum sST2 level, taken from pulmonary artery, with S' parameter in ASD-associated PH. Previous research had shown a significant correlation between serum sST2 with RV systolic function parameters,i.e Tricuspid Annular Plane Systolic Excursion (TAPSE) and Right Ventricle Fractional Area Change (RVFAC), in the PH subjects population due to chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were patients registered in the Congenital HeARt Disease in adult and Pulmonary Hypertension (COHARD-PH) registry, Yogyakarta, Indonesia whom recruited between January 2017 and April 2018 period. 8 The inclusion criteria of this study were1) adult (≄ 18 years old) uncorrected secundum ASD; 2) patients had been undergone right heart catheterization (RHC) and confirmed PAH, and 3) patients had sinus rhythm in electrocardiogram. The exclusion criteria of this study were 1) patients with history of myocardial infarction; 2) patients with impaired left ventricular systolic function; 3) patients have significant valve diseases; 4) patients have lung diseases (asthma bronchial, chronic obstructive and restrictive lung diseases, and post lung tuberculosis); 5) patients with diabetes mellitus; 6) patients with chronic renal disease, and 7) patients with a history of malignancy.…”
Section: Subjectmentioning
confidence: 99%
“…In our registry of adult with congenital heart disease and pulmonary hypertension (COHARD-PH registry) and primary PAH, the majority of patients was at age 30-50 years old. 11 These populations have less risk to develop severe and complicated COVID-19. Older ages at > 65 years old are the most vulnerable populations to develop severe COVID-19.…”
Section: The Younger Agementioning
confidence: 99%
“…3,5 The lower body mass index Lower body mass index is observed in patients with PAH, especially CHDassociated PAH. 7,11 The obesity is one of risk factors for developing severe COVID-19.…”
Section: The Female Gendermentioning
confidence: 99%
“…The prevalence of ASD-PAH is 9%–35% worldwide [ 3 ]. In Indonesia, among adult ASD patients registered in the COngenital HeARt Disease in adults and Pulmonary Hypertension (COHARD-PH) registry in our hospital, 67% had developed PAH, and around 20% of them had severe PAH [ 4 ]. Based on correctability criteria for defect closure, only 59.1% of the patients were suitable for closure either by surgery or device [ 4 ].…”
Section: Introductionmentioning
confidence: 99%